Natural Polymeric Nanobiocomposites for Anti-Cancer Drug Delivery Therapeutics: A Recent Update - Arijit Mondal; Amit Kumar Nayak; Prithviraj Chakraborty; Sabyasachi Banerjee; Bankim Chandra Nandy (MDPI AG, 2023)
Cancer is one of the most common lethal diseases and the leading cause of mortality worldwide. Effective cancer treatment is a global problem, and subsequent advancements in nanomedicine are useful as substitute management for anti-cancer agents. Nanotechnology, which is gaining popularity, enables fast-expanding delivery methods in science for curing diseases in a site-specific approach, utilizing natural bioactive substances because several studies have established that natural plant-based bioactive compounds can improve the effectiveness of chemotherapy. Bioactive, in combination with nanotechnology, is an exceptionally alluring and recent development in the fight against cancer. Along with their nutritional advantages, natural bioactive chemicals may be used as chemotherapeutic medications to manage cancer. Alginate, starch, xanthan gum, pectin, guar gum, hyaluronic acid, gelatin, albumin, collagen, cellulose, chitosan, and other biopolymers have been employed successfully in the delivery of medicinal products to particular sites. Due to their biodegradability, natural polymeric nanobiocomposites have garnered much interest in developing novel anti-cancer drug delivery methods. There are several techniques to create biopolymer-based nanoparticle systems. However, these systems must be created in an affordable and environmentally sustainable way to be more readily available, selective, and less hazardous to increase treatment effectiveness. Thus, an extensive comprehension of the various facets and recent developments in natural polymeric nanobiocomposites utilized to deliver anti-cancer drugs is imperative. The present article provides an overview of the latest research and developments in natural polymeric nanobiocomposites, particularly emphasizing their applications in the controlled and targeted delivery of anti-cancer drugs.